ILEOCOLIC INTUSSUSCEPTION: A RARE CASE OF ACUTE INTESTINAL OBSTRUCTION IN ADULTS - Nayab Alia; Fareha Amin (Journal of University Medical & Dental College, 2012)
ABSTRACT Intussusception is a rare cause of acute intestinal obstruction in adults. The etiology, clinical presentation and management of condition is different in adults as compared to pediatrics age group. Pre-operative diagnosis is usually difficult due to non-specific and intermittent nature of symptoms. Ultrasound can be helpful in diagnosing the condition. Target sign or Doughnut sign and sandwitch appearance/pseudo kidney sign are helmark of diagnosis.